Penggunaan Berbagai Jenis Kitosan Sebagai Edible Coating untuk Menjaga Kualitas Fisik Cabai (Capsicum annuum L.) Selama Penyimpanan pada Suhu Berbeda - Hidayah Wirdani; M Idris (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the effect of chitosan, the effect of storage temperature, and the effect of the combination of chitosan and storage temperature on the physical quality of chilies. This research used a Completely Randomized Factorial Design method, the first factor was chili without chitosan coating (K0), and chili with chitosan coating (K1) = shrimp shell, (K2) = crab shell, (K3) = fish scales using the same concentration, namely 9%. The second factor is storage temperature (T1) = low temperature (10°C) and (T2) = room temperature (26-32°C). The changes observed were weight loss, water content, color measurements, as well as texture and aroma based on organoleptic tests (hedonic tests). Data analysis used ANOVA at the 5% level and BNJ follow-up test at the 5% level. The results showed that shrimp chitosan (K1) caused a low reduction in weight loss, namely (0.96%) and could maintain the texture of chili (8.74). Crab chitosan (K2) can maintain the chili aroma value (8.70). Fish scale chitosan (K3) can maintain water content (1.66%) and maintain chili color. Storage at a temperature of 10°C (T1) has an effect on weight loss (0.15%), maintaining water content (2.00), maintaining chili color (L=87.37; a=155.70; b=124.95) and can maintain texture value (12.26) and aroma (11.99). The best treatment combination for weight loss (0.04%), water content (0.74%) and chili color (L=30.00; a=53.00; b=43.13) is fish scale chitosan and temperature 10 °C (K3T1). Meanwhile, the best treatment combination for texture was shrimp chitosan and a temperature of 10°C (K1T1) 4.28 and aroma was crab chitosan and a temperature of 10°C (K2T1) 4.16. Key words: Chili, Chitosan, Temperature.